WILLINGNESS TO PAY DAN ABILITY TO PAY PELANGGAN RUMAH TANGGA SEBAGAI RESPON TERHADAP PELAYANAN AIR BERSIH DARI PDAM KOTA SURAKARTA - Irawan, BRM Bambang (Universitas Negeri Semarang, 2009)
The aim of this research is to estimate the WTP and ATP value of household customers as theirrespond on additional benefit will be received from PDAM programs will be carried out on year 2004.Beside that, this study also analyzes all significance variables affecting WTP and ATP value.This research applying contingent valuation survey method (CVM) using 500 of sample size from37,054 of targeted population covering all PDAM customers in the Solo city. The sampling techniqueapplied is proportionate stratified random sampling, and the analysis tool put on this study iseconometrics with a white heteroskedasticity-consistent standard errors & covariance model (whiteheteroskedasticity-corrected standard errors & covariance model).This research shows that the WTP value is relatively small and the ATP value is about 20% onaverage below the water bill they paid. One of reasons causing the WTP value reasonably small is thatthe respondent being sampled perceives that their answers will only become a Ã¢â‚¬Å“permitÃ¢â‚¬Â for the PDAM tomake a policy of increasing tariff. These yields are also being expected to help the PDAM in takingpolicies relate to water tariff determination particularly from the demand side.Keyword: Willingness to Pay (WTP), Ability to Pay (ATP), Contingen Valuation.